No prescription? No problem: drivers of non-prescribed sale of antibiotics among community drug retail outlets in low and middle income countries: a systematic review of qualitative studies - Sewunet Admasu Belachew (BMC Public Health, 2021)
Abstract Background Non-prescription dispensing of antibiotics, one of the main sources of antibiotic misuse or over use, is a global challenge with detrimental public health consequences including acceleration of the development of antimicrobial resistance, and is facilitated by various intrinsic and extrinsic drivers. The current review aimed to systematically summarise and synthesise the qualitative literature regarding drivers of non-prescribed sale of antibiotics among community drug retail outlets in low and middle income countries. Methods Four electronic databases (PubMed, CINAHL, Scopus and Google Scholar) and reference lists of the relevant articles were searched. The Joanna Briggs Institute’s Critical Appraisal Checklist for qualitative studies was used to assess the quality of included studies. The enhancing transparency in reporting the synthesis of qualitative research statement was used to guide reporting of results. Data were coded using NVivo 12 software and analysed using both inductive and deductive thematic analysis. Results A total of 23 articles underwent full text review and 12 of these met the inclusion criteria. Four main themes were identified in relation to facilitators of non-prescribed sale of antibiotics among community drug retail outlets: i) the business orientation of community drug retail outlets and tension between professionalism and commercialism; ii) customers’ demand pressure and expectation; iii); absence of or a lax enforcement of regulations; and iv) community drug retail outlet staff’s lack of knowledge and poor attitudes about antibiotics use and scope of practice regarding provision. Conclusions This review identified several potentially amendable reasons in relation to over the counter dispensing of antibiotics. To contain the rise of antibiotic misuse or over use by targeting the primary drivers, this review suggests the need for strict law enforcement or enacting new strong regulation to control antibiotic dispensing, continuous and overarching refresher training for community drug retail outlet staff about antibiotic stewardship, and holding public awareness campaigns regarding rational antibiotic use.